Analysis of Technological Pedagogical and Content Knowledge of Accounting Pre-Service Teachers - Mudrikah, Saringatun; Santoso, Jarot Tri Bowo (Universitas Negeri Semarang, 2021)
This research aims to analyze and compare the level of mastery of Technological Pedagogical and Content Knowledge (TPACK) of the accounting pre-service teachers. This is quantitative survey research. The population is all accounting pre-service teachers who are taking the Learning Design and Strategy course in the even semester of the 2019/2020 academic year, totaling 119 students. The whole sample is used as the research population. The data are collected using a survey method in the form of personal measurements (Self-report-measure) using a questionnaire. The results show the TPACK components including Content Knowledge, Technological Knowledge, Pedagogical Content Knowledge, Technological Content Knowledge, Technological Pedagogical Knowledge, and Technological Pedagogical Content Knowledge in the three classes are in a good category, except that class A in the Pedagogical Knowledge component which has a fair category. The findings conclude that all accounting pre-service teachers who are classified by gender, age, experience in technology training, and experience as tutors have good TPACK abilities. Every educational institution and education personnel should conduct TPACK analysis to find out whether the prospective teachers already master the teaching knowledge and concepts to teach well based on the demands and characteristics of 21st-century learning.